Exploring the use of Automated Application in Writing Activities: University Students’ Experiences (Lembaga Pengembangan Kinerja Dosen, 2026)
Abstract : This study explores the experiences of university students in using Automated Writing Evaluation (AWE) tools during English writing activities. Using a qualitative case study approach, five EFL university students were observed and interviewed to examine how they interact with AWE systems, particularly Quillbot, and how they perceive its role in their writing development. The finding revealed that students utilized AWE for grammar correction, vocabulary enhancement, paraphrasing, and idea generation. While the tools were generally perceived as helpful in improving writing accuracy and fostering independence, participants also expressed concerns about over-reliance on automated feedback and the potential erosion of personal writing style. These findings underscore the importance of using AWE critically and in combination with self-reflection and human feedback to support more effective and autonomous writing practices. Keywords: Automated Writing Evaluation; EFL Writing, Student Perceptio;, Self-directed Learning; Writing Technology